Evaluación de la calidad del agua para consumo humano y propuesta de un plan de medidas correctivas en el centro poblado de Marona, Moyobamba 2018 - Fabian Torres, Junior Ivan (2020)
The general objective of this research was to determine the water quality for human consumption and to propose a plan of corrective measures for its improvement in the town of Marona. The specific objectives were to analyze the quality of the water through the mandatory control parameters before and after its domestic treatment, as well as to propose a plan of corrective measures through training for the inhabitants. The presence of total coliforms, thermotolerant coliforms, color, turbidity, residual chlorine and pH of the water were also analyzed. Methodologically, a single group was used under a pre-experimental design with a sample of 39 randomly selected families. In terms of the results, an advance of the villagers in terms of water treatment in their homes was evidenced, showing that after the training, when chlorine was applied, the average total coliforms in the water were reduced from 1241 NMP/100 ml to 16 NMP/100, while the thermotolerant coliforms were reduced from 496 NMP/100 ml to 6.65 NMP/100 ml. With the application of colloidal silver, these two parameters were reduced to 0 NMP/100 ml, which demonstrated the effectiveness of colloidal silver in water treatment. Regarding color and pH, both when chlorine and colloidal silver were applied, these parameters remained within the maximum permissible limit. The turbidity of the water when chlorine was applied did not exceed the maximum permissible limit, while when colloidal silver was applied, on average, the turbidity of the water exceeded this limit. Finally, the presence of 0.325 mg/L of chlorine in the water was found to be within the permissible limit.